Korttidsminne hos häst : en praktisk studie med hästar av olika kön och ålder - Artursson, Elinor; Andersson, Rebecka (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2018)
Short- term memory in horses- a practical study with horses of different gender and age. Today it is known that horses have a well-functioning long-term memory. However, how other parts of the horse´s memory function are an area that requires more research. It is important to understand the function of the memory when handling and training horses. There is a risk of compromising the welfare of the horse in education and training, if the expectations are too high and the horse is assumed to have higher cognitive abilities than it might have. Therefore, horse owners should have insight into how these animals function to avoid confusion and instead strive to keep the horse relaxed and satisfied. Factors, that might affect the short-term memory of the horse, are gender and age. There is currently no concrete answer if these factors are important, since only a few studies have been carried out in the subject. The aim of this study was to investigate the short-term memory of the horse, focusing on age and gender and discuss how it can affect the horse's learning ability. The learning process can be facilitated when the handler understands more about the function of the memory. The use of reinforcement factors as well as delayed punishment justify the idea that horses know what they were doing or should have done. This study therefore contributes with knowledge about the cognitive ability of the horse, so that training of horses will be carried out with understanding and consequently more efficiently. This study investigated the short- term memory in horses by using a Y- maze. Twenty horses of different gender and age were tested in their ability to recall a feeding event in one of two buckets. They were divided into four groups; group 1 consisted of five older mares (13-15 years), group 2 consisted of five older geldings (14-18 years), group 3 consisted of five younger mares (3-5 years) and group 4 consisted of five younger geldings (4-5 years). The horses were released immediately after the food delivery or after a delayed release that was 3-18 seconds long. All 20 horses were tested during one day undertaking five trial each (one for each time interval), that resulted in a total of 100 releases. The results were analyzed by using a significance test (Chi2). The result showed neither no significant difference between younger and older horses (p=1.0) nor between mares and geldings (p=0.68). In conclusion, there was no difference in horses’ short- term memory based on their gender or age. Further studies are required to enable a concrete answer to be given how the short-term memory affects the horse's ability to learn and how horse trainers will take a stand on it in education and training of horses.